Development of a CT number calibration audit phantom in photon radiation therapy: A pilot study. Issue 4 (29th February 2020) - Nakao, Minoru; Ozawa, Shuichi; Miura, Hideharu; Yamada, Kiyoshi; Habara, Kosaku; Hayata, Masahiro; Kusaba, Hayate; Kawahara, Daisuke; Miki, Kentaro; Nakashima, Takeo; Ochi, Yusuke; Tsuda, Shintaro; et al.
Abstract : Purpose: In photon radiation therapy, computed tomography (CT) numbers are converted into values for mass density (MD) or relative electron density to water (RED). CT‐MD or CT‐RED calibration tables are relevant for human body dose calculation in an inhomogeneous medium. CT‐MD or CT‐RED calibration tables are influenced by patient imaging (CT scanner manufacturer, scanning parameters, and patient size), the calibration process (tissue‐equivalent phantom manufacturer, and selection of tissue‐equivalent material), differences between tissue‐equivalent materials and standard tissues, and the dose calculation algorithm applied; however, a CT number calibration audit has not been established. The purposes of this study were to develop a postal audit phantom, and to establish a CT number calibration audit process. Methods: A conventional stoichiometric calibration conducts a least square fit of the relationships between the MD, material weight, and measured CT number, using two parameters. In this study, a new stoichiometric CT number calibration scheme has been empirically established, using three parameters to harmonize the calculated CT number with the measured CT number for air and lung tissue. In addition, the suitable material set and the minimal number of materials required for stoichiometric CT number calibration were determined. The MDs and elemental weights from the International Commission on Radiological Protection Publication 110 were used as standard tissue data, to generate the CT‐MD and CT‐RED calibration tables. A small‐sized, CT number calibration phantom was developed for a postal audit, and stoichiometric CT number calibration with the phantom was compared to the CT number calibration tables registered in the radiotherapy treatment planning systems (RTPSs) associated with five radiotherapy institutions. Results: When a least square fit was performed for the stoichiometric CT number calibration with the three parameters, the calculated CT number showed better agreement with the measured CT number. We established stoichiometric CT number calibration using only two materials because the accuracy of the process was determined not by the number of used materials but by the number of elements contained. The stoichiometric CT number calibration was comparable to the tissue‐substitute calibration, with a dose difference less than 1%. An outline of the CT number calibration audit was demonstrated through a multi‐institutional study. Conclusions: We established a new stoichiometric CT number calibration method for validating the CT number calibration tables registered in RTPSs. We also developed a CT number calibration phantom for a postal audit, which was verified by the performances of multiple CT scanners located at several institutions. The new stoichiometric CT number calibration has the advantages of being performed using only two materials, and decreasing the difference between the calculated and measured CT numbers for air and lung tissue. In the future, a postal CT number calibration audit might be achievable using a smaller phantom.